Yoga for firefighters: Evaluation of a quality improvement program in California fire departments. (October 2022) - Floyd, Erin; Rackelmann, Sonia; McQuaide, Shannon; Hartogensis, Wendy; Mehling, Wolf
Abstract: Background: Firefighters experience high levels of physical and mental challenges. Yoga interventions have suggested benefits for firefighters. Methods: This study reports results from a quality improvement assessment at fire departments with a 10-class yoga program. Main outcome is the total score on the Functional Movement Scale (FMS), an observer-based objective performance measure. A score of at least 14 [range 0–20] is considered as protective against injury. Secondary outcome is the score on the Multidimensional Assessment of Interoceptive Awareness (MAIA) questionnaire, a self-report measure for interoceptive bodily awareness as a parameter for a mechanism of action with yoga. We used descriptive statistics and regression analyses. Results: Both total FMS and MAIA scores improved statistically significantly. The strongest performance improvement was seen in trunk stability. The mean FMS score improved from below 14 to 14 and higher indicating a decrease in the risk for injury. Changes in FMS and MAIA did not appear to be correlated. Discussion: Despite the limitation of the study design, the findings support the potential benefits from a yoga program for firefighters.